Preparation of 6-Monohalo-β-cyclodextrin Derivatives with Selectively Methylated Rims via Diazonium Salts - Lebedinskiy, Konstantin; Jindřich, Jindřich (ACS omega, 2023)
A series of 6-monohalo (Cl, Br, and I) β-cyclodextrin derivatives with various types of methylations were synthesized via a diazotization/nucleophilic displacement reaction from the corresponding methylated cyclodextrin amines. All four starting compounds (6A-amino-6A-deoxy derivatives of native β-CD, per-6-O-methyl-, per-2,3-O-methyl-, and per-2,3,6-O-methyl-β-CD) were found to have different reactivities under the same reaction conditions. Unsubstituted and fully per-O-methylated cyclodextrin amines undergo fast transformation, giving lower yields of the monohalogenated product. The selectively methylated cyclodextrin amines react remarkably slower and provide almost complete conversion into the desired monohalogenated compound. A pure product was, in several cases, successfully isolated with simple purification techniques (extraction and precipitation), allowing large-scale preparations. This new method opens the way for preparing poorly investigated monofunctionalized selectively methylated cyclodextrins.